IMPACT OF SHADOW ECONOMY ON PRACTICAL ENTREPRENEURS IN ONDO STATE - Musa, Maigari; Daniel, Etong Tima; Terkula , Zangu Paul; Chigozie, Chukwuonye (Kashere Journal of Management Sciences, 2025)
This study investigates the influence of the shadow economy on practical entrepreneurs in Ondo State, Nigeria. The target population comprised 291 shadow economy entrepreneurs, from which a sample size of 169 participants was selected using purposive sampling based on specific criteria related to active entrepreneurial engagement. A descriptive survey design was adopted, and quantitative data were collected through a structured questionnaire. Multiple Linear Regression Analysis was employed to examine the relationships between the independent variables (market share, growth, and welfare) and the dependent variable (performance of practical entrepreneurs). The findings reveal that market share, growth, and welfare each have a positive and statistically significant influence on practical entrepreneurs operating within the shadow economy. Specifically, growth and welfare were found to significantly impact entrepreneurial success, contrary to initial null hypotheses. Based on these findings, the study recommends strategic efforts to enhance entrepreneurs' market share, promote sustainable growth practices, and improve stakeholder welfare. Furthermore, policy interventions aimed at formalizing shadow economy activities, providing skills development opportunities, and facilitating access to financial resources are imperative to support the long-term success of practical entrepreneurs.